Graphene oxide-crown ether compound and sodium ion battery negative electrode material containing same
By using graphene oxide-crown ether composite as the negative electrode material of sodium ion battery, the problems of instability and migration of sodium ion in graphite materials are solved, and the effect of improving electrode insertion/desodium capacity and extending the cycle life of the battery is achieved.
Patent Information
- Application Number
- CN202411611298.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-04
AI Technical Summary
The existing sodium ion battery negative electrode material graphite has increased battery impedance and reduced Coulomb efficiency due to unstable sodium ion embedding and difficulty in migration.
Graphene oxide-crown ether composite is used as the negative electrode material, and graphene oxide is reacted with crown ether sulfonamide and/or benzo crown ether sulfonamide in the presence of tetraalkylammonium hydroxide to form a composite material with a large layer spacing and rich oxygen-containing functional groups.
It improves the sodium storage site of the material, promotes the intercalation and de-extraction of sodium ions, enhances the intercalation/de-sodium capacity of the electrode, extends the cycle life of the battery, and reduces the repeated consumption of electrolytes.
Smart Images

Figure BDA0005130959840000061 
Figure BDA0005130959840000081 
Figure BDA0005130959840000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries. Specifically, the present invention relates to a graphene oxide-crown ether composite that can be used to prepare a negative electrode material for a sodium ion battery, and a negative electrode material for a sodium ion battery comprising the graphene oxide-crown ether composite. The present invention also relates to a negative electrode for a sodium ion battery and a sodium ion battery comprising the negative electrode material for a sodium ion battery. Background Art
[0002] In recent years, sodium-ion batteries have attracted widespread attention as an alternative to lithium-ion batteries.
[0003] Graphite materials that can be used to prepare negative electrodes for sodium-ion batteries are the earliest studied and most commercialized negative electrode materials due to their good conductivity, high crystallinity, good layered structure and charge-discharge voltage platform. However, studies have found that graphite cannot be perfectly used in sodium-ion batteries because it is difficult for sodium ions to embed into the graphite interlayer to form a stable compound.
[0004] For sodium-ion batteries, the radius of sodium ions is larger than that of lithium ions, and the intercalation compound of sodium ions and graphite has positive binding energy. Therefore, the insertion / extraction of sodium ions in the graphite layers cannot be spontaneous thermodynamically. Even if they are successfully inserted, the migration of sodium ions in the graphite layers is also very difficult. At present, the commonly used negative electrode material for sodium-ion batteries is hard carbon. However, there are still side reactions between hard carbon and electrolytes, and the solid electrolyte interface (SEI) is constantly dissolving and reforming, which will lead to increased impedance and reduced coulombic efficiency of sodium-ion batteries.
[0005] Research has found that real graphite materials often have certain lattice defects, which can react with sodium ions to form multi-carbon compounds, but the corresponding reversible capacity of sodium-ion batteries is very low, only about 35 mAh / g. In order to increase the sodium storage capacity of graphite, some people have used ether electrolyte solvents instead of traditional ester electrolyte solvents, and used the solvent co-embedding mechanism to form Na-solvent molecules-graphite ternary intercalation compounds to indirectly store sodium. In theory, this complex can be reversibly inserted and removed between graphite layers, and the actual capacity can reach about 150 to about 200 mAh / g.
[0006] Although the use of ether electrolytes can significantly improve the sodium storage capacity of graphite, the electrochemical window of ether-based electrolytes is relatively narrow, which greatly limits its application in actual production and life. In theory, negative electrode materials represented by graphite will form SEI films during the charge and discharge process. However, under the solvent co-embedding mechanism, the SEI film on the surface of the graphite negative electrode will prevent the embedding of solvent molecules, making the sodiumization process of the solvent molecules difficult.
[0007] At present, there is still a huge market demand for the development of new sodium-ion battery negative electrode materials. Summary of the invention
[0008] Technical issues
[0009] In view of the problems existing in the prior art described in the above background technology section, the object of the present invention is to provide a graphene oxide-crown ether composite that can be used to prepare a negative electrode material for a sodium ion battery, and a negative electrode material for a sodium ion battery comprising the graphene oxide-crown ether composite. The object of the present invention is also to provide a sodium ion battery negative electrode and a sodium ion battery comprising the negative electrode material for a sodium ion battery.
[0010] Technical Solution
[0011] In order to achieve the above object, the present invention adopts the following technical solutions:
[0012] Scheme 1: A graphene oxide-crown ether complex, wherein the graphene oxide-crown ether complex is obtained by reacting graphene oxide with crown ether sulfonamide and / or benzocrown ether sulfonamide in the presence of tetraalkylammonium hydroxide as a catalyst.
[0013] Scheme 2: The graphene oxide-crown ether complex according to Scheme 1 above, wherein the crown ether sulfonamide is selected from one or more of 15-crown-5 sulfonamide and 18-crown-6 sulfonamide.
[0014] Scheme 3: A graphene oxide-crown ether composite according to Scheme 1 above, wherein the benzocrown ether sulfonamide is selected from one or more of benzo-15-crown-5 sulfonamide, dibenzo-15-crown-5 sulfonamide, benzo-18-crown-6 sulfonamide and dibenzo-18-crown-6 sulfonamide.
[0015] Scheme 4: The graphene oxide-crown ether composite according to any one of Schemes 1 to 3 above, wherein the tetraalkylammonium hydroxide is selected from tetrabutylammonium hydroxide.
[0016] Scheme 5: A graphene oxide-crown ether complex according to any one of Schemes 1 to 4 above, wherein in the reaction of the graphene oxide with crown ether sulfonamide and / or benzocrown ether sulfonamide, the weight ratio of the graphene oxide as reaction raw materials to crown ether sulfonamide and / or benzocrown ether sulfonamide is about 1:(0.9-1.1), preferably about 1:1.
[0017] Scheme 6: A graphene oxide-crown ether complex according to any one of Schemes 1 to 4 above, wherein in the reaction of the graphene oxide with crown ether sulfonamide and / or benzocrown ether sulfonamide, the amount of tetraalkylammonium hydroxide used as a reaction catalyst is about 0.4 to about 0.6 times, preferably 0.5 times, the weight of the graphene oxide.
[0018] Scheme 7: The graphene oxide-crown ether composite according to any one of Schemes 1 to 6 above, wherein the reaction of the graphene oxide with crown ether sulfonamide and / or benzocrown ether sulfonamide comprises the following steps:
[0019] Step 1: ultrasonically treating the aqueous solution of graphene oxide at a temperature below about 5° C. for more than about 24 hours;
[0020] Step 2: adding the aqueous solution of crown ether sulfonamide and / or benzocrown ether sulfonamide and the aqueous solution of tetraalkylammonium hydroxide or a mixed aqueous solution thereof to the ultrasonically treated aqueous solution of graphene oxide obtained in step 1, and mixing them uniformly;
[0021] Step 3: subjecting the mixed aqueous solution obtained in step 2 to a hydrothermal reaction at a temperature of about 75 to about 85° C., preferably about 80° C., for example, for more than about 12 hours to obtain the graphene oxide-crown ether composite; and
[0022] Optional step 4: subjecting the graphene oxide-crown ether composite directly obtained from step 3 to washing, filtering and / or drying treatment.
[0023] Scheme 8: The graphene oxide-crown ether composite according to Scheme 7 above, wherein the concentration of the aqueous solution of graphene oxide used in step 1 is in the range of about 0.03 g / mL to about 0.07 g / mL, preferably about 0.05 g / mL.
[0024] Scheme 9: The graphene oxide-crown ether complex according to Scheme 7 or 8 above, wherein the concentration of the aqueous solution of crown ether sulfonamide and / or benzocrown ether sulfonamide used in step 2 is in the range of about 0.04 g / mL to about 0.06 g / mL, preferably about 0.05 g / mL.
[0025] Scheme 10: The graphene oxide-crown ether composite according to any one of Schemes 7 to 9 above, wherein the concentration of the aqueous solution of tetraalkylammonium hydroxide used in step 2 is in the range of about 0.05 g / mL to about 0.07 g / mL, preferably about 0.06 g / mL.
[0026] Scheme 11: The graphene oxide-crown ether composite according to any one of Schemes 1 to 10 above, wherein the graphene oxide is obtained by a process comprising the following steps:
[0027] Step a: Treating graphite with a strong protonic acid at room temperature to obtain a graphite intercalation compound,
[0028] Using about 15 to about 20 mL of the strong protonic acid per gram of graphite; and
[0029] Step b: oxidizing the graphite intercalation compound obtained in step a with a strong oxidant to obtain the graphene oxide.
[0030] Scheme 12: The graphene oxide-crown ether composite according to Scheme 11 above, wherein the strong protonic acid comprises concentrated sulfuric acid with a concentration of at least about 98 wt% and concentrated nitric acid with a concentration of at least about 98 wt% in a volume ratio in the range of about (2.9-3.1):1, preferably about 3:1.
[0031] Scheme 13: The graphene oxide-crown ether composite according to Scheme 11 or 12 above, wherein the strong oxidant comprises acidic potassium permanganate.
[0032] Scheme 14: A graphene oxide-crown ether composite according to any one of Schemes 11 to 13 above, wherein the strong oxidant comprises concentrated sulfuric acid having a concentration of at least about 98 wt % and about 4 to about 6 wt %, preferably about 5 wt %, based on the weight of the graphite intercalation compound, and about 9 to about 11 wt %, preferably about 10 wt %, of potassium permanganate.
[0033] Scheme 15: The graphene oxide-crown ether composite according to any one of Schemes 1 to 14 above, wherein the crown ether sulfonamide and / or benzocrown ether sulfonamide is obtained by reacting the crown ether and / or benzocrown ether with aminosulfonic acid.
[0034] Scheme 16: The graphene oxide-crown ether complex according to Scheme 15 above, wherein the molar ratio of the crown ether and / or benzocrown ether to the aminosulfonic acid is in the range of about 1:(0.9-1.1), preferably 1:1.
[0035] Scheme 17: A negative electrode material for a sodium ion battery, comprising a graphene oxide-crown ether composite according to any one of Schemes 1 to 16 above.
[0036] Scheme 18: A sodium ion battery negative electrode, comprising the sodium ion battery negative electrode material according to Scheme 17 above.
[0037] Option 19: A sodium ion battery, comprising the sodium ion battery negative electrode according to Option 18 above.
[0038] Technical Effects
[0039] The invention adopts cheap and readily available artificial graphite, and obtains graphene oxide with a large interlayer spacing after being treated with a strong oxidant. Then, the graphene oxide is used as a substrate, and crown ether sulfonamide is used as a modification medium, and a stable graphene oxide-crown ether composite material is generated by, for example, a nucleophilic addition reaction. This composite material has a large interlayer spacing and rich oxygen-containing functional groups, which can increase the sodium storage site of the material and facilitate the insertion and removal of sodium ions. At the same time, the crown ether (especially 15-crown-5), which is a macromolecular cyclic compound, has a large space inside (about 170 to about 220 pm), and can preferentially capture Na in the electrolyte. + (diameter of about 190 pm), forming Na + —Ether complexes strengthen the sodium adsorption and storage process on the surface of the material, and can generate a solid electrolyte membrane with high mechanical strength and good flexibility in situ on the surface of the negative electrode, which can prevent the solvation of sodium ions with solvent molecules in the electrolyte, reduce the repeated consumption of electrolytes, increase the sodium insertion / de-insertion capacity of the electrode, and extend the battery cycle life. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without paying creative work belong to the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on normal conditions.
[0041] The endpoints and any values of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. The term "about" used in the present invention means that the modified numeral can fluctuate within the range of ±20%, ±15%, ±10%, ±5% or ±2% of the numeral. For numerical ranges, the endpoint values of each scope, the endpoint values of each scope and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in the present invention.
[0042] In a first aspect, the present invention provides a graphene oxide-crown ether composite.
[0043] The graphene oxide-crown ether composite according to the first aspect of the present invention can be used to prepare a negative electrode material for a sodium ion battery, which is obtained by reacting graphene oxide with crown ether sulfonamide and / or benzocrown ether sulfonamide in the presence of tetraalkylammonium hydroxide as a catalyst.
[0044] Each raw material used in the reaction will be described in detail below.
[0045] Graphene oxide:
[0046] In the first aspect of the present invention, the graphene oxide refers to the oxide of graphene, generally represented by GO, and its color is brownish yellow. The graphene oxide products available on the market are generally in powder, flake or solution form. After oxidation, the oxygen-containing functional groups on the graphene oxide increase, making its properties more active than unoxidized graphene, and its properties can be improved through various reactions with oxygen-containing functional groups. As a single-layer material peeled off from graphite oxide, graphene oxide can be stably present in aqueous solution and polar solvents due to the introduction of a large number of oxygen-containing groups on the surface and edges. After oxidation treatment, graphene oxide still maintains the layered structure of graphite, but many oxygen-containing functional groups are introduced on each layer of graphene monoliths. The introduction of these oxygen-containing functional groups makes the single graphene structure very complicated. The single-layer structure of the graphene oxide, for example, has the following exemplary structural formula:
[0047]
[0048] The graphene oxide used in the first aspect of the present invention may be a commercially available commodity, or may be prepared by a method known in the art.
[0049] For example, in an exemplary embodiment of the present invention, the graphene oxide may be obtained by a process including the following steps a and b.
[0050] The step a comprises treating graphite with a strong protonic acid at room temperature to obtain a graphite intercalation compound.
[0051] The strong protonic acid may, for example, include a mixture of concentrated sulfuric acid having a concentration of at least about 98 wt % and concentrated nitric acid having a concentration of at least about 98 wt % in a volume ratio of about (2.9-3.1):1 (e.g., about 3:1), and about 15 to about 20 mL, preferably about 17 mL, of the strong protonic acid is used per gram of graphite.
[0052] For example, in a preferred embodiment, the graphite intercalation compound can be prepared by the following process: adding washed and dried graphite (about 3 g) to a mixed acid of about 3:1 in a volume ratio of about 98% by weight of concentrated sulfuric acid and fuming concentrated nitric acid (about 50 mL in total) at room temperature, stirring for about 24 hours and slowly adding the reaction mixture to deionized water to dilute the acid concentration in the reaction system to about 10% by weight or less. After the mixture is cooled to room temperature, the insoluble matter is washed with deionized water, and after the insoluble matter is centrifuged, it is vacuum dried at a temperature of about 60° C. to obtain a graphite intercalation compound in the form of a solid powder.
[0053] The step b comprises oxidizing the graphite intercalation compound obtained in the step a with a strong oxidant to obtain the graphene oxide.
[0054] Among them, as the strong oxidant, for example, acidic potassium permanganate can be used, which preferably contains concentrated sulfuric acid with a concentration of at least about 98 weight % based on the weight of the graphite intercalation compound and about 4 to about 6 weight % (for example, about 5 weight %) of potassium permanganate based on the weight of the graphite intercalation compound.
[0055] For example, in a preferred embodiment, the graphene oxide can be prepared by the following process: taking a certain weight of a graphite intercalation compound in the form of a solid powder, adding about 10 weight % of concentrated sulfuric acid with a concentration of at least about 98 weight % based on the weight of the graphite intercalation compound and about 5 weight % of potassium permanganate based on the weight of the graphite intercalation compound, mixing evenly, adding deionized water to dilute the sulfuric acid in the mixture to less than 5 weight %, continuing the reaction under stirring for at least about 24 hours, then adding a hydrogen peroxide solution with a concentration of at least about 30 weight % until the mixture changes from red to purple and then to golden yellow, then, washing the precipitate with dilute hydrochloric acid and deionized water and centrifuging, respectively, and finally vacuum drying the graphene oxide in the form of a solid powder at a temperature of at least about 60° C. to obtain dry graphene oxide.
[0056] Crown ether sulfonamide and / or benzocrown ether sulfonamide:
[0057] In a preferred embodiment, the crown ether sulfonamide may be selected from one or more of 15-crown-5 sulfonamide and 18-crown-6 sulfonamide, with 15-crown-5 sulfonamide being particularly preferred.
[0058] In another preferred embodiment, the benzocrown ether sulfonamide can be selected from one or more of benzo-15-crown-5 sulfonamide, dibenzo-15-crown-5 sulfonamide, benzo-18-crown-6 sulfonamide and dibenzo-18-crown-6 sulfonamide, particularly preferably one or more of benzo-15-crown-5 sulfonamide and dibenzo-15-crown-5 sulfonamide.
[0059] In another preferred embodiment of the first aspect of the present invention, the crown ether sulfonamide and / or benzocrown ether sulfonamide can be directly obtained by commercial purchase, or can be prepared by a method known in the art.
[0060] For example, in an exemplary embodiment of the present invention, the crown ether sulfonamide and / or benzocrown ether sulfonamide is obtained by reacting a crown ether and / or benzocrown ether with aminosulfonic acid, wherein in the reaction, the molar ratio of the crown ether and / or benzocrown ether to the aminosulfonic acid is preferably about 1:(0.9-1.1), more preferably 1:1.
[0061] Specifically, the preparation process may include: cooling a solution of the crown ether and / or benzocrown ether in an organic solvent (e.g., tetrahydrofuran) with a concentration of about 0.7 to about 0.9% by weight (e.g., about 0.8% by weight) to below about 0°C under nitrogen protection, and then slowly dripping an aqueous solution of aminosulfonic acid with a concentration of about 0.7 to about 0.9% by weight (e.g., about 0.8% by weight), stirring for about 10 hours or more to react. After the reaction is completed, quicklime is added until no gas is observed to be produced in the reaction system, thereby neutralizing the excess acid in the reaction system. The resulting mixture is subjected to rotary evaporation to remove the organic solvent to obtain a viscous oily substance, which is then recrystallized with chloroform, and the solid obtained by recrystallization is vacuum dried at a temperature of about 70°C to obtain a dried crown ether sulfonamide and / or benzocrown ether sulfonamide compound.
[0062] For example, taking 15-crown-5, benzobenzo-15-crown-5 and dibenzo-15-crown-5, which are preferably used in the present invention, as examples, their reaction equations with aminosulfonic acid are shown below to obtain 15-crown-5 sulfonamide, benzo-15-crown-5 sulfonamide and dibenzo-15-crown-5 sulfonamide, respectively:
[0063]
[0064]
[0065] Tetraalkylammonium hydroxide:
[0066] In the reaction process of the graphene oxide and the crown ether sulfonamide and / or benzocrown ether sulfonamide, the catalyst used includes the tetraalkylammonium hydroxide. Preferably, the alkyl group is selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl or tert-butyl, identically or differently and independently of each other, at each occurrence. In a particularly preferred embodiment, tetrabutylammonium hydroxide can be used as the catalyst, in particular tetra-n-butylammonium hydroxide.
[0067] In a preferred embodiment of the first aspect of the present invention, the weight ratio of the graphene oxide as the reaction raw material for preparing the graphene oxide-crown ether composite to the crown ether sulfonamide and / or benzocrown ether sulfonamide is in the range of about 1:(0.9-1.1), for example, about 1:0.95, about 1:1 or about 1:1.05. The amount of the crown ether sulfonamide and / or benzocrown ether sulfonamide used herein should not be less than about 0.9 times of the graphene oxide, otherwise the reaction will not be completely carried out and the yield will be low; nor should it be more than about 1.1 times, otherwise undesirable side reactions may easily occur.
[0068] In another preferred embodiment of the first aspect of the present invention, the amount of the tetraalkylammonium hydroxide used as a reaction catalyst is about 0.4 to about 0.6 times the weight of the graphene oxide, such as about 0.45 times, about 0.5 times or about 0.55 times. The amount of the tetraalkylammonium hydroxide used here should not be less than about 0.4 times the weight of the graphene oxide, otherwise the catalytic effect cannot reach the best; it should not exceed about 0.6 times, too much catalyst causes waste and cannot improve the reaction yield.
[0069] In a further preferred embodiment of the first aspect of the present invention, the graphene oxide-crown ether composite according to the first aspect of the present invention can be obtained by a process comprising the following steps.
[0070] Step 1:
[0071] The step 1 includes ultrasonically treating the aqueous solution of graphene oxide in an ice water bath for more than 24 hours to obtain activated graphene oxide. Ultrasonic treatment can improve the dispersibility of graphene oxide in the solvent, making it more uniformly dispersed and avoiding agglomeration, and at the same time can expand the interlayer spacing of graphene oxide.
[0072] Here, the concentration of the aqueous solution of graphene oxide is not particularly limited. For example, in a preferred embodiment, a graphene oxide aqueous solution having a concentration in the range of about 0.03 to about 0.07 g / mL, such as about 0.04 g / mL, about 0.05 g / mL or about 0.06 g / mL is used. Here, the concentration of the aqueous solution of graphene oxide should not be too large, for example, it should not exceed about 0.07 mg / mL, otherwise the graphene oxide may not be sufficiently dispersible, and the concentration should not be too small, for example, it should not be less than about 0.03 mg / mL, otherwise the yield of the subsequent reaction may be reduced.
[0073] In addition, here, the ultrasonic treatment time is long, which may cause the temperature of the aqueous solution to rise. Too high a temperature may affect the dispersion effect of graphene oxide, so it is necessary to use the ice water bath to control the temperature of the graphene oxide aqueous solution to below about 5°C.
[0074] In addition, here, the time for ultrasonically treating the graphene oxide aqueous solution should not be too short, for example, it should not be less than about 24 hours. Insufficient ultrasonic time will lead to insufficient dispersion of graphene oxide and affect the subsequent reaction results.
[0075] Step 2:
[0076] The step 2 comprises adding the aqueous solution of the crown ether sulfonamide and / or benzocrown ether sulfonamide and the aqueous solution of the tetraalkylammonium hydroxide or a mixed aqueous solution thereof to the ultrasonically treated graphene oxide aqueous solution obtained in step 1, and mixing them uniformly.
[0077] Here, the crown ether sulfonamide and / or benzocrown ether sulfonamide and the tetraalkylammonium hydroxide can be separately formulated into aqueous solutions and added to the ultrasonically treated graphene oxide aqueous solution, or the crown ether sulfonamide and / or benzocrown ether sulfonamide and the tetraalkylammonium hydroxide can be formulated into a mixed aqueous solution together and added together to the ultrasonically treated graphene oxide aqueous solution.
[0078] The concentration of the aqueous solution of the crown ether sulfonamide and / or benzocrown ether sulfonamide is not particularly limited, but in a preferred embodiment, the concentration of the aqueous solution of the crown ether sulfonamide and / or benzocrown ether sulfonamide is set in the range of about 0.04 to about 0.06 g / mL, for example, about 0.05 g / mL. Here, the concentration of the aqueous solution of the crown ether sulfonamide and / or benzocrown ether sulfonamide should not be too large, for example, should not exceed about 0.06 g / mL, otherwise undesirable side reactions may easily occur, and the concentration should not be too small, for example, should not be less than about 0.04 g / mL, otherwise the reaction may not be completed.
[0079] The concentration of the aqueous solution of tetraalkylammonium hydroxide is not particularly limited, but in a preferred embodiment, the concentration of the aqueous solution of tetraalkylammonium hydroxide can be set in the range of about 0.05 to about 0.07 g / mL, for example, about 0.06 g / mL. Here, the concentration of the aqueous solution of tetraalkylammonium hydroxide should not be too large, for example, it should not exceed about 0.07 g / mL, otherwise undesirable side reactions may easily occur, and the concentration should not be too small, for example, it should not be less than about 0.05 g / mL, otherwise the effect of the catalytic reaction may be poor.
[0080] Step 3:
[0081] The step 3 comprises subjecting the mixed aqueous solution obtained in step 2 to a hydrothermal reaction at a temperature of about 75 to 85° C., preferably at a temperature of about 80° C., for example, for more than about 12 hours to obtain the graphene oxide-crown ether composite.
[0082] Here, the temperature of the hydrothermal reaction of the mixed solution should not be too high, for example, should not exceed about 85° C., otherwise the reactants are prone to decomposition; nor should it be too low, for example, should not be lower than about 75° C., otherwise the reaction may not be complete.
[0083] In addition, the hydrothermal reaction time should not be too short, for example, it should not be less than about 12 hours, otherwise the reaction will be incomplete and the yield will be low; of course, it does not need to be too long, for example, it should not exceed 15 hours, otherwise the energy consumption will be high and cause unnecessary waste.
[0084] In a further preferred embodiment, the process for preparing the graphene oxide-crown ether composite according to the first invention as described above optionally further comprises the following step 4.
[0085] The step 4 includes subjecting the graphene oxide-crown ether complex directly obtained from the step 3 to washing, filtering and / or drying. For example, in a preferred embodiment, the reaction product "graphene oxide-crown ether complex" directly obtained in step 3 is subjected to multiple washings with deionized water and centrifugal separation, and finally vacuum dried at about 70° C. to obtain a dried graphene oxide-crown ether complex.
[0086] In the second aspect of the present invention, the present invention further provides a negative electrode material for a sodium ion battery, comprising the graphene oxide-crown ether composite as described above according to the first aspect of the present invention.
[0087] Here, the sodium ion battery negative electrode material may further include other materials such as a binder (e.g. sodium carboxymethyl cellulose) and a conductive agent (e.g. conductive carbon black). The weight ratio of the graphene oxide-crown ether composite as the negative electrode active material to the binder and the conductive agent may be in the range of about 95:(1-3):(2-4), for example, about 95:2:3.
[0088] In the third aspect of the present invention, the present invention further provides a sodium ion battery negative electrode, which comprises a sodium ion battery negative electrode material according to the second aspect of the present invention as described above.
[0089] Here, the battery negative electrode can be formed, for example, by coating a slurry containing the sodium ion battery negative electrode material and a solvent on a negative electrode current collector (such as aluminum foil, etc.) and drying the slurry. The solvent can be, for example, deionized water.
[0090] In a fourth aspect of the present invention, the present invention further provides a sodium ion battery, which comprises the sodium ion battery negative electrode according to the third aspect of the present invention as described above.
[0091] It should be noted that the relevant features and preferred features described above with respect to the graphene oxide-crown ether composite in the first aspect of the present invention are also applicable to the second, third and fourth aspects of the present invention.
[0092] The present invention is further described in detail below with reference to specific embodiments and comparative examples.
[0093] The chemical raw materials used in the following examples and comparative examples were all commercially available analytically pure reagents.
[0094] Preparation Example 1:
[0095] (1) Preparation of graphene oxide:
[0096] At room temperature, about 50 mL of concentrated sulfuric acid with a concentration of at least 98% by weight and concentrated nitric acid with a concentration of at least 98% by weight in a volume ratio of about 3:1 are taken, mixed evenly, and about 3 g of washed and dried graphite is added and stirred for about 24 hours. The reaction solution is then slowly added to about 1000 mL of deionized water to dilute the acid. After the mixture is cooled to room temperature, the insoluble matter is washed with deionized water, and the insoluble matter is centrifuged and vacuum dried at a temperature of about 60° C. to obtain a graphite intercalation compound in the form of a solid powder. To the graphite intercalation compound in the form of a solid powder, about 10 wt % concentrated sulfuric acid (about 0.3 g) and about 5 wt % potassium permanganate (about 0.15 g) based on the total weight are added, and after mixing evenly, about 100 mL of deionized water is added, and magnetic stirring is performed for about 24 hours, and a hydrogen peroxide solution with a concentration of about 30 wt % is added dropwise until the mixture solution changes from red to purple and then to golden yellow, and then the insoluble matter in the mixture is washed with dilute hydrochloric acid and deionized water, respectively, and the insoluble matter is centrifuged and dried in vacuo at a temperature of about 60° C. to obtain graphene oxide.
[0097] (2) Preparation of crown ether sulfonamide compounds:
[0098] A tetrahydrofuran solution of 15-crown-5 with a concentration of about 0.8 wt% is placed in a three-necked flask and stirred evenly under nitrogen protection, the reaction system is cooled to below about 0°C, and then an aqueous solution of aminosulfonic acid with a concentration of about 0.8 wt% is slowly added dropwise to the reaction system, and magnetic stirring is performed for about 10 hours. After the reaction is completed, quicklime is added until no gas output is observed in the reaction system, thereby neutralizing excess acid. The liquid in the reaction system is rotary evaporated to remove most of the tetrahydrofuran and water as solvents to obtain a viscous oily substance, which is then recrystallized from chloroform, and the obtained recrystallized solid is vacuum dried at a temperature of about 70°C to obtain a 15-crown-5 sulfonamide compound.
[0099] (3) Preparation of graphene oxide-crown ether composite:
[0100] Prepare equal masses of graphene oxide powder obtained from the above step (1) and 15-crown-5 sulfonamide obtained from the above step (2), and tetrabutylammonium hydroxide equivalent to half the weight of the graphene oxide powder. First, the graphene oxide is prepared into an aqueous solution with a concentration of about 0.05 g / mL, and the graphene oxide aqueous solution is ultrasonically treated in an ice water bath for about 24 hours to obtain an activated graphene oxide aqueous solution. Then, the 15-crown-5 sulfonamide aqueous solution with a concentration of about 0.05 g / mL and the tetrabutylammonium hydroxide aqueous solution with a concentration of about 0.06 g / mL are added to the ultrasonically treated graphene oxide aqueous solution. The mixed aqueous solution is mixed evenly by magnetic stirring, transferred to a hydrothermal synthesis reactor, and hydrothermally reacted at a temperature of about 80° C. for about 12 hours. The obtained solid reaction product is washed with deionized water several times and then centrifuged. Finally, the reaction product is vacuum dried at a temperature of about 70° C. to obtain the graphene oxide-crown ether complex, wherein the crown ether type is 15-crown-5.
[0101] Preparation Example 2:
[0102] The graphene-crown ether composite was prepared by a process similar to that of Preparation Example 1, except that the crown ether species was replaced with benzo-15-crown-5.
[0103] Preparation Example 3:
[0104] The graphene-crown ether composite was prepared by a process similar to that of Preparation Example 1, except that the crown ether species was replaced with dibenzo-15-crown-5.
[0105] Embodiments 1 to 3:
[0106] In order to verify the actual application effect of the negative electrode material comprising the graphene-crown ether composite prepared by Preparation Examples 1 to 3 in sodium ion batteries, the negative electrode materials comprising the graphene-crown ether composite obtained by Preparation Examples 1 to 3 were respectively assembled into button-type sodium ion batteries, and the electrochemical properties of the batteries were tested.
[0107] The sodium ion battery includes a negative electrode as a working electrode, a positive electrode as a counter electrode, an electrolyte and a separator.
[0108] The working electrode is prepared by the following process: the graphene-crown ether composite, conductive carbon and sodium carboxymethyl cellulose are uniformly mixed in deionized water in a mass ratio of 95:2:3 to obtain a suspension with a solid content of about 53 weight %, and then the suspension is coated on an aluminum foil, and then dried in an oven at a temperature of about 75° C. for about 3 hours to obtain a negative electrode as a working electrode.
[0109] A sodium sheet was used as the counter electrode.
[0110] The electrolyte includes a solution of about 1 mol / L NaPF6 in ethylene carbonate (EC), dimethyl carbonate (DEC) and fluoroethylene carbonate (FEC) (wherein EC:DEC:FEC=49:49:2 volume %).
[0111] The diaphragm is made of glass fiber.
[0112] The assembly of the button-type sodium ion battery was carried out in a glove box with oxygen and water contents both below about 1 ppm.
[0113] Comparative Examples 1 to 2:
[0114] Sodium ion batteries were assembled in a similar process to Examples 1 to 3, except that the graphene-crown ether composite used as the negative electrode material was replaced with graphite (Comparative Example 1) and graphene oxide (Comparative Example 2), respectively.
[0115] The electrochemical performance of the sodium ion batteries of Examples 1 to 3 and Comparative Examples 1 to 2 was tested. The test was performed on an electrochemical workstation CHI600 of Shanghai Chenhua. The test voltage was about 1.5 to about 3.95V, and the current density was about 30mA / g. The electrochemical performance data results of the tested sodium ion batteries are shown in Table 1 below.
[0116] Table 1:
[0117]
[0118] It can be seen from the performance result data in Table 1 above that the charging capacity of the sodium ion batteries of Examples 1 to 3 of the present invention all reaches about 1.8 mAh or more, while the charging capacity of the sodium ion battery of Comparative Example 2 is only about 1.42 mAh, and the charging capacity of the sodium ion battery of Comparative Example 1 is even only about 0.18 mAh.
[0119] The first efficiency of the sodium ion batteries of Examples 1 to 3 of the present invention all reached more than 82%, while Comparative Example 1 produced a large amount of gas during the first charging stage, and there was no way to test the first efficiency later. The first efficiency of the sodium ion battery of Comparative Example 2 was only about 77.51%.
[0120] The capacity retention rates of the sodium ion batteries of Examples 1 to 3 of the present invention after 50 cycles at 25°C all reached more than about 99.5%, while the capacity retention rate of the sodium ion battery of Comparative Example 1 after 50 cycles at 25°C could not be measured, and the capacity retention rate of the sodium ion battery of Comparative Example 2 after 50 cycles at 25°C was only 99.21%.
[0121] By comparing the above data, it can be seen that under the same test conditions, Examples 1 to 3 of the present invention have improved charging capacity compared to Comparative Examples 1 and 2, indicating that the composite material of the present invention has better sodium storage effect than single graphite or graphene oxide, and the improvement of the first effect indicates that the composite material can release the embedded sodium while improving the sodium storage capacity, and is not easy to cause dead sodium and sodium precipitation. Therefore, using the graphene oxide-crown ether composite of the present invention as the negative electrode active material can improve the sodium insertion / extraction capacity of the electrode and extend the cycle life of the prepared sodium ion battery.
[0122] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions claimed to be protected by the present invention.
Claims
1. A graphene oxide-crown ether composite, characterized in that The graphene oxide-crown ether composite is obtained by reacting graphene oxide with crown ether sulfonamide and / or benzocrown ether sulfonamide in the presence of tetraalkylammonium hydroxide as a catalyst.
2. The graphene oxide-crown ether composite according to claim 1, characterized in that The crown ether sulfonamide is selected from one or more of 15-crown-5 sulfonamide and 18-crown-6 sulfonamide; and / or The benzocrown ether sulfonamide is selected from one or more of benzo-15-crown-5 sulfonamide, dibenzo-15-crown-5 sulfonamide, benzo-18-crown-6 sulfonamide and dibenzo-18-crown-6 sulfonamide; and / or The tetraalkylammonium hydroxide is selected from tetrabutylammonium hydroxide.
3. The graphene oxide-crown ether composite according to claim 1, characterized in that In the reaction of the graphene oxide with crown ether sulfonamide and / or benzocrown ether sulfonamide, The weight ratio of graphene oxide and crown ether sulfonamide and / or benzocrown ether sulfonamide as reaction raw materials is 1:(0.9-1.1); and / or The amount of tetraalkylammonium hydroxide used as a reaction catalyst is 0.4 to 0.6 times the weight of the graphene oxide.
4. The graphene oxide-crown ether composite according to any one of claims 1 to 3, characterized in that The reaction of graphene oxide with crown ether sulfonamide and / or benzocrown ether sulfonamide comprises the following steps: Step 1: ultrasonically treating an aqueous solution of graphene oxide preferably having a concentration in the range of 0.03 g / mL to 0.07 g / mL at a temperature below 5° C. for more than 24 hours; Step 2: adding an aqueous solution of the crown ether sulfonamide and / or benzocrown ether sulfonamide preferably having a concentration in the range of 0.04 g / mL to 0.06 g / mL and an aqueous solution of the tetraalkylammonium hydroxide preferably having a concentration in the range of 0.05 g / mL to 0.07 g / mL or a mixed aqueous solution thereof to the ultrasonically treated graphene oxide aqueous solution obtained in step 1, and mixing them uniformly; Step 3: subjecting the mixed aqueous solution obtained in step 2 to a hydrothermal reaction at a temperature of 75 to 85° C. for more than 12 hours to obtain the graphene oxide-crown ether composite; and Optional step 4: subjecting the graphene oxide-crown ether composite directly obtained from step 3 to washing, filtering and / or drying treatment.
5. The graphene oxide-crown ether composite according to any one of claims 1 to 3, characterized in that The graphene oxide is obtained by a process comprising the following steps: Step a: treating graphite with a strong protonic acid at room temperature to obtain a graphite intercalation compound, wherein 15 to 20 mL of the strong protonic acid is used per gram of graphite; and Step b: oxidizing the graphite intercalation compound obtained in step a with a strong oxidant to obtain the graphene oxide.
6. The graphene oxide-crown ether composite according to claim 5, characterized in that The strong protonic acid comprises concentrated sulfuric acid having a concentration of at least 98 wt % and concentrated nitric acid having a concentration of at least 98 wt % in a volume ratio of (2.9-3.1):1; and / or The strong oxidizing agent comprises acidic potassium permanganate, preferably comprises 9 to 11 wt % concentrated sulfuric acid at a concentration of at least 98 wt % and 4 to 6 wt % potassium permanganate based on the weight of the graphite intercalation compound.
7. The graphene oxide-crown ether composite according to any one of claims 1 to 3, characterized in that The crown ether sulfonamide and / or benzocrown ether sulfonamide is obtained by reacting the crown ether and / or benzocrown ether with aminosulfonic acid, wherein the molar ratio of the crown ether and / or benzocrown ether to the aminosulfonic acid is preferably 1:(0.9-1.1).
8. A sodium ion battery negative electrode material, characterized in that: The sodium ion battery negative electrode material comprises the graphene oxide-crown ether composite according to any one of claims 1 to 7.
9. A sodium ion battery negative electrode, characterized in that: The sodium ion battery negative electrode comprises the sodium ion battery negative electrode material according to claim 8.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium ion battery negative electrode according to claim 9.